Failure to Rescue After Abdominal Surgery: an Audit on Incidence and Predictors - Pandit, Narendra; Deo, Kunal B; Awale, Laligen; Bhattarai, Sameer; Yadav, Tek Narayan (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Failure-to-rescue (FTR), defined as death after a surgical complication, is a quality metric that is an important variable affecting mortality rates in hospitals. This study aims to analyze complications, FTR rates, and its predictors at the index hospital setting. Methods: This was a retrospective cohort study performed at an academic hospital from 2015 to 2020 in the Department of Surgical Gastroenterology. We included all patients who had major complications following elective major benign or malignant abdominal surgeries. The primary and secondary endpoint was FTR rates and the overall major complications and deaths, re-operation rate, and its predictors respectively. Results: Among 762 patients, the rate of any major complication was 14.9% . The overall mortality rate was 2.8%. However, the mortality rate among patients with complications was 27.4% (FTR). Twenty-seven (52.9%) patients underwent re-operation for complications, out of which 70% survived. Three (21.4%) patients had a delay in prompt diagnosis and interventions of complications and had FTR due to the anastomotic leak and bleeding. The ASA grade, co-morbidities, re-operation, and nature of the disease (benign vs. malignant) did not predict the FTR. Conclusion: This study conducted at an academic, low-volume center had higher rates of FTR. It can be further reduced by both prompt and appropriate interventions of postoperative complications in a multidisciplinary setup.